Experimental, Numerical and Analytical Assessment of a new Multi-Level Damper with Steel Trapezoidal Plates - Ebrahimian, Haleh; Hojatkashani, Ata; Firoozi Nezamabadi, Maryam; Hosseini, Mahmood (Springer Science and Business Media Deutschland GmbH, 2025)
Metallic dampers are a common energy-dissipating tool in structural engineering. Meanwhile, these dampers have a disadvantage compared to viscous rivals, as the yielding force must be exceeded to activate the device, limiting their effectiveness across a range of potential events. Multi-level control can be employed as a way of addressing this limitation. In this paper, a novel multi-level yielding energy dissipating device, termed the Trapezoidal Multi-Level Yielding Damper (TMYD), is introduced. The TMYD employs pairs of trapezoidal plates as mechanical fuses, with each pair designed to absorb energy during specific earthquake intensities. While the number of plates is not analytically constrained, this study focuses on three pairs. The hysteretic behavior of TMYD is investigated through both experimental and numerical methods. Uniaxial tests are conducted to determine the axial force–displacement curve of a full scale prototype. A continuum-scale numerical model of the device is developed and validated against experimental results for further analysis. Additionally, analytical methods are employed to derive formulas for the optimal design of the damper. The findings demonstrate that the suggested damper has high energy absorption capabilities through reliable hysteretic loops, enhancing the performance of structures subjected to earthquake loads of varying intensities. The force–displacement characteristics of TMYD, including yield load, dissipated energy, and effective stiffness over consecutive loading cycles, are calculated. Furthermore, the experimental, analytical and numerical results are found to be in close agreement. © The Author(s), under exclusive licence to Shiraz University 2024.
Keywords: Energy dissipation; Hysteretic behavior; Metallic yield damper; Multi-level damper; Passive control